LIVING QUALITY SURROUNDING THE CIPINANG CORRECTIONAL FACILITY BASED ON THE RESIDENTS PERCEPTION - Aji Nur Hidayat; Endrawati Fatimah; Anindita Ramadhani (Universitas Trisakti, 2022)
The Law of the Republic of Indonesia Number 12 of 1995 concerning Corrections mandates that Correctional Facility be established in every Regency and City. Meanwhile, several works of literature state that Correctional Facility must meet the criteria, namely having a certain distance or far from densely populated settlements to reasons for the safety and comfort of residents. This research was conducted in settlements around Cipinang Correctional Facility, DKI Jakarta. Cipinang Correctional Facility was initially established in 1912, located on the outskirts of Jakarta and far from residential areas. However, the Correctional Facility is currently located in the middle of a dense settlement. This study aims to identify the perception of the people living in the vicinity of the existence of the Cipinang Correctional Facility in terms of security and comfort. The security variable indicators include insecurity and anxiety, while the variable comfort indicator is a sense of being disturbed by the activities and negative image of the Correctional Facility. The data was obtained through a questionnaire survey with Likert scale measurements and analyzed by the scoring method. The results showed that the people living around the Cipinang Correctional Facility had a good perception of the Cipinang Correctional Facility in terms of security and comfort aspects.